Skeletal, dental and soft tissue changes in Class III patients treated with fixed appliances and lower premolar extractions - Abu Alhaija Elham S.J; Al-Khateeb Susan N. (Sciendo, 2011)
Background: Mild Class III malocclusions can be treated by upper incisor proclination and lower incisor retroclination following extraction of the lower first premolars.